A durable Ni3S2 coated mesh with reversible transition between superhydrophobicity and underwater superoleophobicity for efficient oil-water separation. Issue 3 (June 2022) - Yin, Xiaoli; Yu, Sirong; Wang, Bingying; Wang, Liyuan; Wang, Jun; Liu, Enyang; Li, Hao; Chen, Zhong
Abstract: Oil leakage and the discharge of industrial oil/water mixtures have posed a serious threat to the water environment and ecosystem. With the purpose of tackling this issue, a Ni3 S2 coated mesh with switchable wettability was fabricated for efficient oil-water separation. Surface morphology and chemical compositions of the coated mesh were characterized to analyze the formation mechanism and their influence on surface wettability. The reversible transition between superhydrophobicity and underwater superoleophobicity allows the coated mesh to selectively separate heavy or light oil under gravity, respectively. A T-shaped tube with a superhydrophobic mesh and an underwater superoleophobic mesh was proposed to overcome the limitation of oil density and the conventionally necessary intrusion pressure to achieve continuous and efficient separation. This system functioned well in separating complex mixtures including oil-hot water mixtures and oil-in-water emulsions. Therefore, this Ni3 S2 nanorods grown on stainless steel mesh present a promising solution towards oily water treatment. Highlights: A fluorine-free Ni3 S2 coated mesh with switchable wettability was fabricated. This coated mesh exhibits excellent durability to resist external damages. The coated mesh functions well in separating heavy or light oil-water mixtures. The mesh is able to separate oil-hot water mixtures and oil-in-water emulsions.